Tinjauan Literatur: Pemanfaatan Teknologi Informasi untuk Meningkatkan Mutu Pelayanan Publik - Sakir, Ahmad Rosandi (LPPM STIA Lancang Kuning Dumai, 2024)
The numerous complaints from the public regarding the poor quality of public services have become an urgent issue that the government must address. Along with the rapid advancement of information technology, many institutions and agencies have begun restructuring their systems to improve service quality for the public. The utilization of information technology is expected to provide ease and efficiency in delivering services to the public. This research aims to identify the extent to which the implementation of information technology contributes to improving the quality of public services. Using a descriptive qualitative method, this research relies on secondary data such as literature, articles, journals, regulations, and websites relevant to this topic. Data validity is tested through triangulation, while the theory applied in this study refers to service quality concepts, which include the dimensions of tangibles, reliability, responsiveness, assurance, and empathy. The findings of the research indicate that the application of information technology in enhancing public service quality has not yet been fully optimized. One of the challenges is seen in the dimension of tangibles, where digitalization has not been fully utilized, requiring physical storage space for an increasing number of documents. In terms of reliability, technology-based services are highly dependent on communication network conditions, which are affected by weather. During heavy rain or strong winds, network quality often weakens or gets disrupted, slowing down data processing and management, and potentially leading to inaccuracies. Additionally, responsiveness has not reached its full potential, as services are still slow and processing times remain too lengthy.